Services écosystémiques fournis par les espaces agricoles - Tibi, Anaïs (éditions Quae, 2018)
Based on analyses by agricultural and legal experts, this work offers food for thought on using the law to include the notion of ecosystem service in soil protection. It has been written as part of the research programme â€œSoil cultivation, ecosystem services and compensation. Agricultural and legal aspectsâ€ within the Institute of legal studies on town planning, construction and environment.